Institutional Commitments and Challenges to Achieve a Sustainable and Inclusive Development Strategy: The Case of Persons with Disabilities - Zimbrón Pérez, Guadalupe (2019)
The article analyzes the inclusion of people with disabilities (PWD) to the labor market from a theoretical perspective. It presents a theoretical and empirical panorama of labor inclusion of PWD in Yucatán, analyzing different perspectives of international, national and local instruments used to quantify and classify disabilities. The methodology was carried out through a documentary review, consulting different research works, statistical reports and the development of public policies. According to Amartya Sen (1990) and his theory of human development, it is emphasized the need for economically active participation of the PWD in the market in decent work, as a way forward towards sustainable development and as a target in 2030 agenda. As a result, a chronology of public policies is presented toward the evolution of the concept of PWD and its social and labor inclusion, and the actual strategies that are used to increase the labor inclusion of PWD, as the advances that are made in the country and the city in this topic.